2020
DOI: 10.7150/ijms.43832
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Malic Enzyme 2 Indicates Pathological and Clinical Significance in Oral Squamous Cell Carcinoma

Abstract: Our study investigated the expression of malic enzyme 2 (ME2) in human oral squamous cell carcinoma (OSCC) and associated pathological and clinical pattern. We demonstrated that human OSCC tissues expressed a high level of ME2, and the overexpression of ME2 is closely connected to a high pathological grade, lymphatic metastasis, large tumor size and human papillomavirus (HPV) (P < 0.001). Similarly, high levels of ME2 expression in OSCC tissue were shown to be correlated with poor prognosis (P < 0.05). The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies have shown that in HNCs, ALDH1 is mainly regulated by retinoic acid compounds and other oncogenic pathways such as MUC1-C/ERK and WNT/β-catenin ( 191 ), but also by the AKT signaling pathway ( 192 , 193 ). ALDH1A1 increases TUBB3 expression, which down-regulates PTEN and promotes cell proliferation, migration, and invasion ( 194 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%
“…Studies have shown that in HNCs, ALDH1 is mainly regulated by retinoic acid compounds and other oncogenic pathways such as MUC1-C/ERK and WNT/β-catenin ( 191 ), but also by the AKT signaling pathway ( 192 , 193 ). ALDH1A1 increases TUBB3 expression, which down-regulates PTEN and promotes cell proliferation, migration, and invasion ( 194 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%
“…ME1 is a potential oncogene product linked to energy metabolism, redox status, and epithelial to mesenchymal transition (EMT) in squamous cell carcinoma (oral, head, and neck), breast cancer, and gastric cancer. ME2 is overexpressed in human primary oral squamous cell carcinoma tissue and in lung carcinoma tissue for helping tumor cell proliferation and colony formation. , ME2 is also known to promote cell proliferation, invasion, and migration of glioma cells in glioblastoma . ME3, a paralogous isoform of ME2, is localized in mitochondria, and its aberrant expression contributes to the carcinogenesis of pancreatic cancer …”
mentioning
confidence: 99%
“…9−11 ME2 is overexpressed in human primary oral squamous cell carcinoma tissue and in lung carcinoma tissue for helping tumor cell proliferation and colony formation. 12,13 ME2 is also known to promote cell proliferation, invasion, and migration of glioma cells in glioblastoma. 14 ME3, a paralogous isoform of ME2, is localized in mitochondria, and its aberrant expression contributes to the carcinogenesis of pancreatic cancer.…”
mentioning
confidence: 99%